Synthesis of Potentially Bioactive Hydrazones of Pyrimidine and 1,3,5-Triazine - Gomktsyan, T. A.; Shainova, R. S.; Dovlatyan, M. V.; Yengoyan, A. P. (ՀԱԱՀ հիմնադրամ)
The reaction of the pyrimidine and 1,3,5-triazine hydrazides with various aldehydes formed corresponding hydrazones. Synthesized compounds are endowed with potential bioactivity. In laboratory-vegetation screening, the obtained compounds showed a pronounced stimulating effect on plant growth. The activity of the tested compounds varied in the range of 46–88 % as compared to heteroauxin. Compounds that showed an activity above 70 % in the experiment will be selected for deeper study and further field tests.
Keywords: Agronomy and Agroecology